Ghost business - DeLuca, Jen (Berkley Romance, 2025)
"Clashing ghost tours lead to a sizzling romantic rivalry in the second romance in the new series from USA Today bestselling author Jen DeLuca. Boneyard Key, Florida, is the only home Sophie has ever known. Her love for its supernatural history has flourished into a career, as she guides the one and only ghost tour through the town's can't-miss haunted spots. And while her bank account isn't full by any means, her heart is. Or at least, it was. But there's a newcomer in town. The son of a Fortune 500 businessman, former theater kid Tristan has grown his tours from a fraternity fundraiser to a multicity ghost tour conglomerate. It's doing well, but not well enough-if he can't prove that he's solidly in the black by the fall, Dad's going to pull his funding, spelling the end of his career. Boneyard Key, with its haunted reputation, seems like the perfect place to boost his bottom line. When the two ghost tours clash, Sophie's expletive-filled rant goes viral, and the rivals strike up a deal. Whoever has the most successful business by summer's end stays, while the loser must ghost. But the more Tristan comes to appreciate Boneyard Key, the more Sophie comes to appreciate Tristan, and what starts as begrudging respect becomes something spicier. Can they put their feuding businesses aside to make room for a chance at love, or is Boneyard Key too small for two ghost tours?"--